Re-evaluating large for gestational age: differential effects on perinatal outcomes in term and premature births - Chun-Heng Kuo; Chun-Heng Kuo; Chun-Heng Kuo; Yi-Ling Wu; Chi-Nien Chen; Chi-Nien Chen; Yu-Ru Lo; I-Weng Yen; Kang-Chih Fan; Yi-Yun Tai; Ming-Wei Lin; Chih-Cheng Hsu; et al. (Frontiers in Medicine)
ObjectivePregnancies with large-for-gestational-age (LGA) fetuses are associated with increased risks of various adverse perinatal outcomes. While existing research primarily focuses on term neonates, less is known about preterm neonates. This study aims to explore the risks of adverse maternal and neonatal perinatal outcomes associated with LGA in term neonates and neonates with different degrees of prematurity, compared to appropriate-for-gestational-age (AGA) neonates.MethodsUsing the Birth Reporting Databases (2007–2018) linked to Taiwan's National Health Insurance Research Database, we conducted a retrospective nationwide cohort study of singleton neonates delivered between 24 and 42 weeks of gestation. Based on gestational age at delivery, the enrolled neonates were classified into term (37–42 weeks of gestation), late preterm (34–36 weeks of gestation), moderate preterm (32–33 weeks of gestation), very preterm (28–31 weeks of gestation), and extremely preterm (24–27 weeks of gestation). LGA was defined by the 2013 World Health Organization (WHO) growth standard and the Taiwan growth standard. Perinatal outcomes were compared between LGA and AGA neonates across different gestational age groups.ResultsAmong the 1,602,638 neonates, 44,359 were classified as LGA by the 2013 WHO growth standard. Compared to AGA neonates, LGA neonates in term and late preterm groups exhibited higher risks of primary cesarean section, prolonged labor, neonatal hypoglycemia, birth trauma, hypoxic ischemic encephalopathy, jaundice needing phototherapy, respiratory distress, neonatal intensive care unit (NICU) admission, newborn sepsis, and fetal death. However, most of these risks were not increased in moderate, very, and extremely preterm groups. Conversely, being LGA was associated with lower risks of primary cesarean section (very preterm group), jaundice needing phototherapy (moderate and very preterm groups), respiratory distress (moderate and very preterm groups), NICU admission (moderate and very preterm groups), newborn sepsis (very preterm group), retinopathy of prematurity (late, moderate, and very preterm groups), and bronchopulmonary dysplasia (very preterm group). These findings remained consistent when the Taiwan growth standard was applied.ConclusionBeing LGA is associated with increased risks of perinatal complications in term and late preterm neonates, but not in earlier preterm groups. These findings underscore the importance of tailoring management strategies for LGA neonates to consider different degrees of prematurity.